PENGARUH EMPLOYEE STOCK OPTION PLAN (ESOP) TERHADAP AGENCY PROBLEM - Azib Azib; Vini Yunita Safitri (Jurnal Manajemen Bisnis Performa, 2007)
ABSTRACT Employee Stok Option Plan (ESOP) is an incentive form given by company to employees through giving stock option program as compensation form for good job achievement. Stock option was given to employees, it can be convincing afford to improve company performance. With increasing this company performance, a company able to improve stock- holder welfare. This research intend to find out how much influence of employee stock option plan (ESOP) into agency problem trough firm size estimate and leverage. Data colleted and analyzed through statistic test with using simple regression. Level of civincing using 95% (α= 0.05). Through two sided producing ESOP into Agency Problem, through firm size estimate obtained t-account is 5,984 and t-table is 2,056 its mean H0 is rejected or there are influence. While ESOP into agency problem trough leverage estimate getting t-account 0,762 and t-table 2,056 its mean H0 can be accepted or there is no influence. Keyword : ESOP, option, agency problem, firm size and leverage.